1995
DOI: 10.1111/j.1476-5381.1995.tb16627.x
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene receptors on human pulmonary vascular endothelium

Abstract: 1 Cysteinyl-leukotrienes cause contractions and/or relaxations of human isolated pulmonary vascular preparations. Although, the localization and nature of the receptors through which these effects are mediated have not been fully characterized, some effects are indirect and not mediated via the welldescribed LT1 receptor. 2 In human pulmonary veins (HPV) with an intact endothelium, leukotriene D4 (LTD4) induced contraction above basal tone. This response was observed at lower concentrations of LTD4 in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 23 publications
(44 reference statements)
3
32
0
Order By: Relevance
“…MacLean et al (1993) reported that treatment with L-NAME enhances responses to sumatriptan in human isolated pulmonary artery. Loss of endothelial integrity in human pulmonary artery preparations subjected to cold storage overnight (Ortiz et al, 1995) may explain the ®nding of greater E max values for sumatriptan by MacLean et al (1996) compared to other studies including this one (see above).…”
Section: Role Of the Endothelium In The Responses To 5-ht And Sumatrimentioning
confidence: 82%
See 2 more Smart Citations
“…MacLean et al (1993) reported that treatment with L-NAME enhances responses to sumatriptan in human isolated pulmonary artery. Loss of endothelial integrity in human pulmonary artery preparations subjected to cold storage overnight (Ortiz et al, 1995) may explain the ®nding of greater E max values for sumatriptan by MacLean et al (1996) compared to other studies including this one (see above).…”
Section: Role Of the Endothelium In The Responses To 5-ht And Sumatrimentioning
confidence: 82%
“…at 48C for transport to the laboratory where pulmonary arteries and veins were dissected free from parenchymal tissue and the preparations were cut in rings (3 ± 4 mm length62 ± 5 mm internal diameter). Tissues were used within 3 h of surgery as we have previously shown that preparations stored overnight often failed to show an endothelium-dependent relaxation when stimulated with histamine (Ortiz et al, 1995). In some preparations the endothelium was removed by inserting into the lumen of each ring a roughened wooden stick and rubbing gently the intimal surface of the blood vessel.…”
Section: Preparation Of Human Pulmonary Blood Vesselsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, while a proinflammatory environment down-regulates CysLT 2 receptor expression in human umbilical vein endothelial cells (HUVECs) [42], CysLT 1 receptor expression is induced in HUVECs under such conditions [43]. Furthermore, studies of isolated arteries have demonstrated endothelium-dependent contractions through CysLT 1 receptor signaling [44,45]. Taken together, those observations suggest that a balance of CysLT receptor subtype expression may determine the LT-induced endothelium-dependent vasomotor responses.…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
“…Although the lung resection and pulmonary artery dissection were performed at the most distant point from and completely free of tumour tissue, we cannot rule out a possible influence of the inflammatory neoplastic microenvironment, which may be one limitation of this study. was removed from some pulmonary artery rings, as described previously [14]. Arteries were used within 1 to 5 h post-surgery.…”
Section: Preparation Of Pulmonary Artery Ringsmentioning
confidence: 99%